c+bc-11c-4=13c+4-2

Simple and best practice solution for c+bc-11c-4=13c+4-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for c+bc-11c-4=13c+4-2 equation:


Simplifying
c + bc + -11c + -4 = 13c + 4 + -2

Reorder the terms:
-4 + bc + c + -11c = 13c + 4 + -2

Combine like terms: c + -11c = -10c
-4 + bc + -10c = 13c + 4 + -2

Reorder the terms:
-4 + bc + -10c = 4 + -2 + 13c

Combine like terms: 4 + -2 = 2
-4 + bc + -10c = 2 + 13c

Solving
-4 + bc + -10c = 2 + 13c

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + bc + 4 + -10c = 2 + 4 + 13c

Reorder the terms:
-4 + 4 + bc + -10c = 2 + 4 + 13c

Combine like terms: -4 + 4 = 0
0 + bc + -10c = 2 + 4 + 13c
bc + -10c = 2 + 4 + 13c

Combine like terms: 2 + 4 = 6
bc + -10c = 6 + 13c

Add '10c' to each side of the equation.
bc + -10c + 10c = 6 + 13c + 10c

Combine like terms: -10c + 10c = 0
bc + 0 = 6 + 13c + 10c
bc = 6 + 13c + 10c

Combine like terms: 13c + 10c = 23c
bc = 6 + 23c

Divide each side by 'c'.
b = 6c-1 + 23

Simplifying
b = 6c-1 + 23

Reorder the terms:
b = 23 + 6c-1

See similar equations:

| 2k+10=k+15 | | (8/t-7)-3/t | | 15=2a-2 | | 18+6x+x^2=0 | | 5x-5y=10z | | -4/35/8/7 | | 2(4x+8)=x+7x-2 | | -7=-7x+3(x+5) | | -a+2a=4a+6-2 | | -3y=6/5 | | -4x/7=-12 | | 6x=-6x+144 | | 6x-15=5x-9 | | 5/-5 | | x-3/x= | | 6x/39 | | -5/9w=35 | | 44.95(t-25)=2511.6 | | (a+3b)+(3a-b)i=6+6i | | x×x-3/x= | | x×x-3/x=18 | | 4x^2=57 | | 10v-3=8v+9 | | 3y-3(-33)=2y+2(-33) | | 4b+4b+4b= | | 2=9z-3z+2-6z+4+z | | 3m+6m-10m=3+7-4+m | | .4(7-3x)=9+(4x-1) | | 5x+8x+11x= | | -40x+36x=30x-45 | | 2b^2+36-9=0 | | 4x-3=9x+9 |

Equations solver categories